(untitled) (Pulse, 2017)
Multiple biliary hamartoma (MBH) is a rare cause of multiple benign hepatic lesions. The condition is also known as von Meyenburg complexes, multiple bile duct hamartomas and biliary microhamartomas. MBH is asymptomatic and usually found incidentally where it is important to differentiate from other causes of multiple liver lesions particularly liver metastases. Histologically, they consist of cystic dilatation of the bile duct, encompassed by fibrous stroma. We reported a 74 year old male patient with multiple hepatic lesions which ultrasonographic appearance suggested multiple hepatic cysts. The diagnosis of MBH was made by MRCP of whole abdomen. Recognition of this unusual lesion is essential to avoid confusion with other cystic tumors of the liver specially liver metastases and to learn more about its natural history and response to treatment. Pulse Vol.9 January-December 2016 p.60-63